(untitled) (World Bulletin of Public Health, 2023)
Treatment of patients with congenital facial clefts accompanied by dento-mandibular anomalies and nasal deformities is one of the most difficult tasks of modern dentistry and maxillofacial surgery. Providing qualified care to this group of patients involves multistage surgical interventions, constant dispensary observation and treatment by a number of specialists - surgeons, orthodontists, speech therapists, paediatricians, otorhinolaryngologists.